Prediction of the Network Pharmacology-Based Mechanism for Attenuation of Atherosclerosis in Apolipoprotein E Knockout Mice by Panax notoginseng Saponins. (22nd April 2020) - Long, Linzi; Yu, Zikai; Qu, Hua; Wang, Ning; Guo, Ming; Zhou, Xuezhong; Fu, Changgeng; Gao, Zhuye
Abstract : This study investigated whether Panax notoginseng saponins (PNS) reduced atherosclerotic lesion formation in apolipoprotein E knockout (ApoE-KO) mice and illustrated the potential mechanism for a network pharmacology approach. Pharmacodynamics studies on ApoE-KO mice with atherosclerosis (AS) showed that PNS generated an obvious anti-AS action. Then, we explored the possible mechanisms underlying its anti-AS effect using the network pharmacology approach. The main chemical components and their targets of PNS were collected from TCMSP public database and SymMap. The STRING v11.0 was used to establish the protein-protein interactions of PNS. Furthermore, the Gene Ontology (GO) function and KEGG pathways were analyzed using STRING to investigate the possible mechanisms involved in the anti-AS effect of PNS. The predicted results showed that 27 potential targets regulated by DSLHG were related to AS, including ACTA2, AKT1, BCL2, and BDNF. Mechanistically, the anti-AS effect of PNS was exerted by interfering with multiple signaling pathways, such as AGE-RAGE signaling pathway, fluid shear stress and atherosclerosis, and TNF signaling pathway. Network analysis showed that PNS could generate the anti-AS action by affecting multiple targets and multiple pathways and provides a novel basis to clarify the mechanisms of anti-AS of PNS.